Some aspects of arbitration as a way of settling insurance disputes - Raul-Felix Hodoș; Narcis Păvălașcu (Revista de Studii Financiare, 2019)
The paper aims at briefly reviewing the advantages of arbitration in relation to classical, public justice, on the one hand, and, on the other hand, of specialized arbitration (in insurance) compared to the general arbitration. Alternative dispute resolution has been received in recent decades as a necessary measure not only to relieve the courts of a significant part of the potential cases, but mainly because of the confidential and rapid nature of the procedures adopted. Technological changes brought with them new ways of communicating, and conflicts can now arise not only from lack of communication, but also from the inappropriate communication of information or because of too much information that leads to the loss of the essential data. Exiting the pre-defined formats of the participants on the insurance market must also lead to the adaptation of methods of alternative dispute resolutions, and specialized arbitration is one of the most important ways to choose.